Paraclinical Characteristics of Fatal and Recovered COVID-19 Cases: a Retrospective Study - Elham Goodarzi1; Mohammad Kakavand2; Kobra Rashidi3; Shahram Mamdohi2; Victoria Momenabadi4; Mojgan Navabi2; Hamidreza Abolfathi2; Zaher Khazaei5 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-Cov2). It is a potentially deadly disease with grave consequences for public and global health. This study compared laboratory indices in recovered and fatal COVID-19 cases. Methods: In this descriptiveanalytical cross-sectional study, sampling was conducted using the total count method, and the data was collected from the Borujerd Health Network's Disease Management Center database. From February 20, 2020, to July 21, 2020, 380 patients with positive PCR tests were included. The extracted data was exported into Stata-14 software. To analyze descriptive objectives, mean, percentage, standard deviation, Chi-squared test, and t-test were used. Results: Out of 380 positive COVID-19 cases, 300 patients recovered, and 80 lost their life. More than half of the recovered and fatal cases were men (55.16%). The highest mortality rate belonged to 80 ≤ years (27.5%). Among fatal cases, 38.75% had no underlying disease, and the most common underlying diseases were diabetes (27.5%), chronic hypertension (18.75%), and malignancy (7.5%). Comparison of laboratory indices revealed a significant difference in the mean LHD, Na, K, BUN, BS, PT, AST, ALT, ALP, and ALP Hb between recovered and fatal cases (P <0.05). Conclusion: This finding can help determine patients' prognoses and adjust the treatment approach. Further studies on paraclinical characteristics will shed further light on the pathogenesis of COVID-19 and appropriate treatment measures.